Knowledge, attitude and practice of people regarding rabies in rural area of Jammu: a cross sectional study - Singh, Kamna; Kapoor, Anuj; Gupta, Nidhi (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies although a fatal disease, remains a disease of low public health priority. India, about 18,000 to 20,000 cases is reported every year. Awareness about rabies is very poor among Indian population particularly in rural areas, due to which India and Bangladesh belongs to a high incident countries Methods: Present study was descriptive and cross sectional in nature conducted in village Sai of block R.S. Pura. Data was collected by face to face interview of 200 participants using a pre structured questionnaire. Results: Knowledge about rabies was intermediate as majority of the people (78.5%) have heard about the diseases. About 144 persons enumerated hydrophobia as the most common symptom. Only 48.5% of the study participants knew that it is important to wash the wound with soap and running water and 53.5% respondents were in favor of consulting a doctor. 123 (61.5%) persons understood that rabies can be prevented by proper treatment of animal bite. Conclusions: Our study found that most of the respondents knew that dogs were mainly responsible for transmitting rabies. The recommended first aid for rabies is immediate flushing and washing of the wound with soap and water for a minimum of 15 minutes. This study revealed that most people placed the responsibility for controlling the dog population on the government.